2018
DOI: 10.1097/pts.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Incidents Reported by the General Public in Korea: A Cross-Sectional Study

Abstract: The general public can report their experiences with PSIs. Periodic surveys that target the general public will provide additional data that reflect the level of patient safety from the viewpoint of the general public.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 40 publications
2
36
2
Order By: Relevance
“…The questionnaire was developed and composed to enable comparison with the PSI experiences of the general public. 22 Questionnaire items were developed by referencing literature on the types and characteristics of PSIs 23–25 and previous studies on second victims. 3 26 The draft questionnaire was developed based on repeated discussions held among the entire research team (including two physicians and three nurses who have abundant research experience on patient safety).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed and composed to enable comparison with the PSI experiences of the general public. 22 Questionnaire items were developed by referencing literature on the types and characteristics of PSIs 23–25 and previous studies on second victims. 3 26 The draft questionnaire was developed based on repeated discussions held among the entire research team (including two physicians and three nurses who have abundant research experience on patient safety).…”
Section: Methodsmentioning
confidence: 99%
“…Since nurses may be unfamiliar with terminology related to patient safety, definitions of such terms, including patient safety , medical error , adverse event and patient safety incident , were provided prior to the survey. 23 29 30 The survey was promoted via online blog posts and word-of-mouth among colleagues, and participants were gathered through snowball sampling. Participants were blocked from responding to the questionnaire more than once from the same IP address, to prevent possible repeated participation in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The KOPS was established for the safety of medical institutions; it collects information on patient safety at the national level [4]. The system analyzes the root causes of serious incidents that may occur in relation to patients and provides useful data on the prevalence and causes of medical errors through case record review [19,23].…”
Section: Study Design and Samplementioning
confidence: 99%
“…Incident reports for patient safety in healthcare are considered significant in enhancing patient safety strategies, monitoring, and prevention, as well as in reducing the occurrence of patient safety events [18]. Thus, the reporting of safety events is important for the broad goal of error reduction [19]. Despite the importance of PSIs in clinical settings, most medical institutions focus on acute treatment, so there is a lack of PSI reports in Korea [20].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Ock, Jo, Choi, & Lee [2] Ock, Jo, Choi, & Lee [2] that the community reported incidents of patient safety. As many as 700 people surveyed, 24 (3.4%) and 37 (5.3%) respectively reported that they or their families experienced Patient Safety Incidents (PSI).…”
Section: Introductionmentioning
confidence: 99%